Visitor Attitudes Toward Little Penguins (Eudyptula minor) at Two Australian Zoos - Chiew, Samantha J.; Hemsworth, Paul H.; Melfi, Vicky; Sherwen, Sally L.; Burns, Alicia; Coleman, Grahame J. (Frontiers in Psychology, 2021)
This study compared the attitudes of visitors towards zoo-housed little penguins, their enclosure and visitor experience at two Australian zoos. Visitor attitudes were assessed using an anonymous questionnaire, targeting visitor beliefs and experiences, where visitors were randomly approached at the penguin exhibit after they had finished viewing the penguins. Visitors were given two options to complete the questionnaire, on an iPad during their zoo visit or online (URL sent via email) after their zoo visit. A total of 638 participants (495 at Melbourne Zoo and 143 at Taronga Zoo) completed the questionnaire, 42% were completed onsite during their zoo visit and 58% were completed online after their zoo visit. Most participants were living in Australia, non-zoo members, female, previously or currently owned a pet, aged between 26-35 years and had a University degree. Results showed that the attitude dimensions of visitors were consistent between the two zoos which indicates that these measures of attitudes were stable over time and location. Overall, visitors at both zoos had positive attitudes towards little penguins, penguin welfare, the enclosure and visitor experience. However, there were some differences in visitor attitudes towards the perceived ‘aggressiveness’ and ‘timidness’ of little penguins, ‘negative penguin welfare’, ‘experience with the penguins’, ‘learning’, ‘visual barriers’ and the way visitors rated their overall experience at the penguin enclosure. While the reasons for the differences in visitor attitudes and visitor experience between the zoos were not clear, some factors such as penguin behaviour and enclosure design, may have been attributable to these differences. Also, a relationship was found between visitor attitudes and how visitors rated the welfare of penguins, the enclosure and visitor experience at the enclosure; more positive visitor attitudes were associated with higher ratings of penguin welfare, the enclosure and visitor experience. The practical implications of these results for zoos is unclear because the differences in visitor attitudes were numerically small. This requires further comparisons between zoos or enclosures that are more markedly different than the penguin enclosures in the present study and further research on how visitors assess zoo animals, enclosures and visitor experience.